Trasplante cardiaco en paciente adulto con circulación de Fontan disfuncionante en un centro de alta complejidad cardiovascular en el Perú: reporte de caso - Roger Yoel Conde Moncada; Víctor Robles Velarde; Romel Zamudio Silva; Edwin Amado Masabel Chicoma; Sergio Martín Zavala Castillo; Franz Ronald Soplopuco Palacios (Archivos Peruanos de Cardiología y Cirugía Cardiovascular, 2026)
Fontan circulation failure represents a progressive condition associated with multiorgan dysfunction and increased morbidity and mortality. In this context, heart transplantation has become the definitive treatment for this subgroup of patients. Reported survival rates after heart transplantation in patients with Fontan circulation are approximately 80% at 1 year, 74% at 5 years, and 59% at 10 years. We present the case of a 46-year-old patient with a history of Ebstein anomaly who underwent intracardiac Fontan surgery, which progressed to progressive Fontan circulation failure, and who underwent orthotopic heart transplantation with reconstruction of the pulmonary branches.